Unilateral loss of the swallow tail sign in a patient with idiopathic Parkinson’s disease - Abd Rashid, Anna Misyail; Md Noh, Mohamad Syafeeq Faeez; Yusof Khan, Abdul Hanif Khan; Mohd Yaakob, Mohd Naim; Bahari, Norafida; Basri, Hamidon (Longe Medikal, 2021)
A 66-year-old man with underlying hypertension and dyslipidemia presented with left hand tremor for one year. He also noticed difficulty in initiating movement and slowness in activities of daily living. On examination, he was noted to have mask-like facies with reduced blinking and monotonous speech. There was presence of resting pill-rolling tremor, bradykinesia, and cogwheel rigidity which was worst on the left upper limb. Gait assessment revealed difficulty in standing up, shuffling gait with reduced arm swing which was more prominent on the left side, and turning in numbers. No cerebellar signs and supranuclear palsy were present to suggest Parkinson-plus syndrome. Susceptibility weighted imaging (SWI) showed loss of the swallow tail sign on the right side [Figure 1]. The clinical presentation, supplemented by the imaging findings were concluded to be pathognomonic of idiopathic Parkinson’s disease (IPD), Hoehn & Yahr stage 1. He was started on levodopa and benserazide twice daily with improvement of symptoms.